2013
DOI: 10.1007/s00264-013-2154-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival and radiological results of the Duracon™ total knee arthroplasty

Abstract: PurposeThe aim of this study was to analyse the long-term (>ten years) survival rate and radiological results of the Duracon TKA.MethodsBetween 1992 and 1999 159 Duracon TKA were implanted at our institution. A Kaplan-Meier survival analysis for the endpoints exchange, addition or removal of any component for any reason, revision due to aseptic loosening and mechanical failure was performed. Radiological long-term (>ten years) follow-up (FU) analysis was performed according to the Knee Society Radiographic Eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…A longterm study by Bachmann et al [4] evaluated the survivorship of Duracon TKAs (n = 159 prostheses) and found the mean aseptic survivorship rate of 97.7% and 94.8% after a 10-year and 15-year follow-up, respectively. With the use of radiographic images, Bachmann et al also found good long-term implant stability reflected by little changes or alignment differences after a minimum 10-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A longterm study by Bachmann et al [4] evaluated the survivorship of Duracon TKAs (n = 159 prostheses) and found the mean aseptic survivorship rate of 97.7% and 94.8% after a 10-year and 15-year follow-up, respectively. With the use of radiographic images, Bachmann et al also found good long-term implant stability reflected by little changes or alignment differences after a minimum 10-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, manufacturers and surgeons are continuously developing newer implants and surgical techniques that may increase the implant survivorship and improve the outcomes after this procedure [2,3]. The Duracon knee (Stryker Howmedica, Rutherford, New Jersey) is a worldwide-used device, specifically designed for improved patello-femoral tracking and increased contact between the femorotibial surfaces [2,4].…”
mentioning
confidence: 99%
“…The SR design has a fixed axis of rotation centered about the transepicondylar axis, which maintains ligament tension and substantial contact throughout the range of motion [3]. This is thought to allow for uniform movement, lower contact stress on the inlay, better mid flexion stability, and enables a mechanical advantage of the quadriceps muscles during extension of the knee [3,15,16]. The Triathlon also has flared femoral posterior condyles thought to aid rotation during deep knee flexion [2].…”
Section: Discussionmentioning
confidence: 99%
“…The procedure has proven to be exceptionally reliable in terms of implant longevity, with 20year revision free survival rates between 70.9%-91.0%. [1][2][3][4][5][6][7][8][9][10][11] Unfortunately, achieving a comparable level of subjective clinical success has proven to be elusive. A host of reports evaluating patient reported outcomes after TKA quote up to 20% of patients are not satisfied, often citing continued pain, stiffness, or an 'unnatural' feel to the joint.…”
Section: Introductionmentioning
confidence: 99%